The pillars of society - Ibsen, Henrik,Meyer, Michael Leverson (Bloomsbury, 2013)
'The Pillars of Society' is an absorbing example of Ibsen in his less familiar mood of humane comedy. Though the issues it confronts are no longer urgent, it remains a tightly plotted and beautifully characterised examination of selfish deception and defiance of convention. Published in 1877, 'The Pillars of Society' has been described as the first play to combine the three elements of colloquial dialogue, objectivity, and tightness of plot which are the requirements and characteristics of modern prose drama.
10.5040/9781472590336.00000003